2005
DOI: 10.1007/s10024-005-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Metastasizing Spindle Epithelial Tumor with Thymus-like Differentiation (SETTLE) of the Thyroid

Abstract: Spindle epithelial tumor with thymus-like elements is a rare thyroid lesion of children and young adults thought to be derived from branchial pouch remnants or foci of ectopic thymus. The lesion is poorly understood, and although it was originally believed to follow an indolent clinical course, its potential for late metastasis is becoming generally acknowledged. We have recently seen a unique case of this rare tumor in an 11-year-old boy, in which an unexpected and salient feature is the presence of a microme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Indeed, Erickson [3] noted that 35% of all reported cases of SETTLE had one metastasis during their course, whereas Cheuk [4] noted a significant metastatic rate of 71% for patients with more than 5 years of follow-up after diagnosis. Metastatic disease has also been described up to 22 and 25 years after the initial operative intervention [5,6].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, Erickson [3] noted that 35% of all reported cases of SETTLE had one metastasis during their course, whereas Cheuk [4] noted a significant metastatic rate of 71% for patients with more than 5 years of follow-up after diagnosis. Metastatic disease has also been described up to 22 and 25 years after the initial operative intervention [5,6].…”
Section: Discussionmentioning
confidence: 97%
“…In addition to morphology, immunohistochemistry is important for making the diagnosis of SETTLE. The tumor is typically positive for cytokeratin, vimentin, smooth muscle actin, and muscle-specific actin [2,3,[14][15][16][17][18]. Spindle epithelial tumor with thymus-like elements is typically negative for other markers of thyroid malignancy including thyroglobulin, thyroid transcription factor-1, calcitonin, carcinoembryonic antigen, and S-100.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the disease progression with metastasis development, low mortality rates are observed, demonstrating the indolent course of the tumor. SETTLE may not produce metastasis until many years after the diagnosis (mean of 11 years) and according to case reports with follow-up information, the overall rate of metastasis is of about 20% (2,(8)(9)(10)(12)(13)(14)(15). Otherwise, when the analysis is made only on patients with more than 5 years of follow-up, the incidence increases to 50% (8,(12)(13)(14) with 2 patients developing metastasis more than 20 years after the diagnosis (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Erickson et al [29 ]noted that 35% of all reported cases of SETTLE had one metastasis during their course, whereas Cheuk et al [7 ]noted a significant metastatic rate of 71%.The preferential site of metastasis is the lung, along with the cervical lymph nodes and the kidney. There are no existing guidelines regarding the treatment and follow-up of cases due to a paucity of data about the management of SETTLE tumor.…”
Section: Discussionmentioning
confidence: 99%